Polycarbonate nanocomposites. Part 1. Effect of organoclay structure on morphology and properties - Yoon, P.J.; Hunterb, D.L.; Paul, D.R.
Polycarbonate nanocomposites were prepared by melt processing from a series of organoclays based on sodium montmorillonite exchanged with various amine surfactants. To explore the effects of matrix molecular weight on dispersion, an organoclay was melt-mixed with a medium molecular weight polycarbonate (MMW-PC)and a high molecular weight polycarbonate (HMW-PC)using a twin screw extruder. The effects of surfactant chemical structure on the morphology and physical properties were explored for nanocomposites formed from HMW-PC. Wide angle X-ray scattering, transmission electron microscopy, and stress-strain behavior were employed to nvestigate the nanocomposite morphology and physical properties. The modulus enhancement is greater for nanocomposites formed from HMW-PC than MMW-PC. This trend is attributed to the higher shear stress generated during melt processing. A surfactant having both polyoxyethylene and octadecyl tails shows the most significant improvement in modulus with some of the clay platelets fully exfoliated. However, the nanocomposites formed from a range of other organoclays contained both intercalated tactoids and collapsed clay particles with few, if any, exfoliated platelets.
Keywords: POLYCARBONATE; NANOCOMPOSITES; MELT PROCESSING